Polycentrism in Germany: A Comparative Study for Three City Regions - Wiegandt, Claus-C.; Osterhage, Frank; Haunstein, Stefan (Raumforschung und Raumordnung | Spatial Research and Planning, 2015)
The article takes up the current debate on polycentric urban areas as well as it visualizes the recent patterns of urban development by comparing the three city regions Cologne/Bonn, the eastern Ruhr area and Leipzig/Halle. For this purpose three maps showing the central functional cores, the separation of residential areas and commuting flows are presented and further explained. It shows that the spatial patterns of the three urban regions result from long-term development to which the traditional cores of settlements are still of high importance regarding the city regions. The dissolving of cities towards dispersed urban areas is only visible rudimentarily.
Keywords: Polycentric city region; Visualisation; Spatial development; Post-suburbanisation; Germany; Comparative urban research